Effects of Sallropus androgynus (katuk) leaf extract on growth, fat accumulation and fecal microorganisms in broiler chickens - U Santoso; E Handayani; Suharyanto . (Indonesian Center for Animal Research and Development (ICARD), 2001)
A study was conducted to determine the effects of Sauropus androgynus leaf extract on growth, carcass quality and the number of fecal microorganisms in broiler chickens. Forty-eight male Arbor Acres broiler chickens (21-d-old) obtained from a commercial hatchery were used in the present study. Experiment consisted of four treatment groups with four pen replicates of three broilers allotted randomly to each dietary treatment from day 21-42 old. One group was the control with no additional Sauropus androgynus leaf extract (SAE) (P0), and other three groups were given drinking water supplemented with 1.5 g (PI), 3.0 g (P2) or 4.5 g SAE/l water (P3). The diet used was a commercial mix (Crude protein: 19% and Metabolizable Energy 3200 kcal/kg). Feed intake significantly reduced in P2 or P3 as compared with the control (P<0.05). A decrease in feed conversion ratio was observed in treatment groups as compared with Po (P<0.05). Abdominal fat, neck fat and liver fat content were significantly reduced by SAE (P<0.05), while carcass fat content was not significantly different. Number of fecal Escherichia coli in P1 or P3 (P<0,01) and fecal Streptococcus sp and Salmonella sp. were significantly (P<0,01) reduced by SAE supplementation as compared with the control, while fecal Bacillus subtilis in P2 and Lactobacillus sp. in P1 (P<0,01) were significantly higher as compared with other groups. SAE (P2 or P3) also significantly improved meat taste, shank color but lowered meat color (P<0.05) as compared with the control group. It was found that the number of fecal Streptococcus sp was suitable to predict abdominal fat. In conclusion, the inclusion of SAE at 4.5 g/l drinking water resulted in the best performance and carcass quality. Key words: Sauropus androgynus leaf extract, fat accumulation, broilers